THE INFECTIVE ENDOCARDITIS (PREVENTION, DIAGNOSIS CRITERIA AND TREATMENT): KEY POINTS 2010 - A. A. Demin (Рациональная фармакотерапия в кардиологии, 2016)
Key positions of Guidelines on the prevention, diagnosis, and treatment of infective endocarditis issued by the Task Force of ESC in 2009 are explained in the comments. Recent opinions on these items are presented.